What Can We Do Better for Sustainability in an Uncertain Future? - Xu, Li; Raphaely, T. (Springer Nature, 2017)
Sustainability is a significant challenge confronting a changing world. With an increasingly uncertain future ahead for human wellbeing, achieving, social–ecological sustainability is more than just a simple goal. The new imperative for natural resources management sheds is how to avoid the collapse of social–ecological systems as a result of external shocks triggered by climate change and anthropogenic perturbations. Building up resilient social–ecological systems is therefore an urgent issue for sustainability science. Using water resources management as an example, this paper discusses the need to introduce resilience thinking into sustainability science, how such a thinking should be incorporated into sustainability management for adapting to the growing uncertainties, and how social–ecological resilience can be enhanced.